(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
Political violence can be defined as a form of violence that is subject to political power, whether it is to achieve power, whether to protest, or to eliminate a power and to maintain and sustain a given power. In this general sense, political violence can be separated from the natural meaning of violence, because the power of the center and the ventricle lies in virtually all forms of violence. In other words, violence can be attributed to a kind of physical force and pressure from an institution, an individual or a group over an institution, an individual or another group, in order to force that institution or individuals to do something contrary to their will. Hence, violence is always against desire, will and freedom, and somehow defines its limits. However, given the fact that the freedom of an individual can be precisely at the opposite point in the freedom of another person. By dividing the independent variables of research into 6 factors of religious discrimination, the use of non-native forces, the use of foreign media, participation in elections, political activity, and religious intolerance, it was observed that the impact of the dimensions of the use of foreign media, participation in Elections, political activity, and religious intolerance are meaningful in terms of political violence and can have an impact on the spread of political violence in the region.